2022
DOI: 10.3389/fneur.2022.1004629
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide to botulinum neurotoxin treatment of shoulder spasticity 1: Anatomy, physiology, and goal setting

Abstract: Botulinum neurotoxin type A (BoNT-A) is a first-line treatment option for post-stroke spasticity, reducing pain and involuntary movements and helping to restore function. BoNT-A is frequently injected into the arm, wrist, hand and/or finger muscles, but less often into the shoulder muscles, despite clinical trials demonstrating improvements in pain and function after shoulder BoNT-A injection. In part 1 of this two-part practical guide, we present an experts' consensus on the use of BoNT-A injections in the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…A recent 2022 expert consensus by Jacinto et al adapted the five post-stroke spasticity patterns into two shoulder spasticity patterns: “A” (adduction, elevation, flexion and internal rotation of shoulder) with the presence of elevation and flexion, vs. extension in Pattern “B” (abduction or adduction, extension and internal rotation of the shoulder. It is notable that Jacinto et al’s expert panel made further suggestions to define patterns [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent 2022 expert consensus by Jacinto et al adapted the five post-stroke spasticity patterns into two shoulder spasticity patterns: “A” (adduction, elevation, flexion and internal rotation of shoulder) with the presence of elevation and flexion, vs. extension in Pattern “B” (abduction or adduction, extension and internal rotation of the shoulder. It is notable that Jacinto et al’s expert panel made further suggestions to define patterns [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the literature often focuses on the pectoralis major and subscapularis, there are many muscles implicated in shoulder spasticity including the deltoid, trapezius, teres major and minor, pectoralis major, subscapularis, supra- and infra- spinatus, coracobrachialis, latissimus dorsi and the long head of the biceps and triceps brachii muscles [ 8 ]. The choice of muscles to inject is largely due to personal bias or experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shoulder spasticity can affect adduction, elevation, flexion, and internal rotation of the shoulder; abduction only; or adduction, extension, and internal rotation of the shoulder. 1 To treat spasticity for an adducted shoulder, injections are typically administered to the pectoralis major, teres major, and subscapularis muscle. In most cases, it is sufficient to inject only the pectoralis major and teres major as the primary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, botulinum neurotoxin has been shown to be safe and effective in reducing muscle tone for focal spasticity of the upper limb and in improving active upper limb function. 1 Shoulder muscles have been included in clinical trials of botulinum toxin for upper limb spasticity and have demonstrated improvements. [2][3][4][5][6][7][8] Injection with botulinum toxin has been shown to improve shoulder function and reduce pain in an observational study of chronic poststroke spasticity.…”
Section: Introductionmentioning
confidence: 99%